In Search of Progressive America - Hurenkamp, Menno, 1971-; Becker, Frans; Kazin, Michael, 1948- (Book collections on Project MUSE., 2008)
The era of conservative dominance in the U.S. appears to be stumbling. But is the Left ready to step into the breach? In Search of Progressive America is a collection of ten essays by prominent writers that seeks to address the current state of promise and debate on the portside of U.S. politics.